Formalize the Software Quality Measurement for Heterogeneous Requirements - Edwin, Mit; Cheah, Wai Shiang (2015)
There are two main challenges in measuring quality of software requirements: (i) There is no single model that can precisely represent the properties of heterogeneous requirements, and (ii) how to derive the quantitative measurement of the requirement properties that can be used to measure the software requirements quality? The issue of quality measurement is to define the benchmark or baseline used to transform the qualitative measurement to the quantitative measurement, and to date there are lack of particular rules or properties used to assess whether the propose software requirements fulfills the criteria. Therefore, this paper presents and discusses the framework of a new formal platform for assessing the quality of heterogeneous software requirements, which are obtain from open innovations. Hence, with this model the reliability of the software to be produced is known. This is an important study which, lead to the reduction of software failure in particular for safety-critical system